Cardiopulmonary reanimation in pediatric and neonatal: the evolution of care throughout history (Research, Society and Development, 2022)
The object of this study is the records on the care provided in cardiopulmonary resuscitation, by the author Paluel J. Flagg, delimited to newborns and children, through the experiences reported in The Art of Resuscitation, published in 1944. The time of the study traveled through the mid-twentieth century, with the United States as its backdrop. The objectives were to describe and analyze the care provided to newborns and children, recorded in the work of Paluel J. Flagg, from 1944, regarding cardiopulmonary resuscitation. The images come from this and other works, found on the website Neonatology on the web. The analysis of texts and images was based on the micro-history and the concept of translation and transcreation by Haroldo Campos. Political and economic contexts generated incentives for study and attention to care in situations of cardiopulmonary resuscitation during this period. During the advancement of time there were changes in the scenario for the care of newborns and children, at that time techniques and guidelines were developed around their management, as well as instruments to assist in the treatment. It is clear that through experience, with mistakes and successes, knowledge was built. And that, despite technological advances, there are similarities in the procedures and in the essence of emergency care and cardiopulmonary resuscitation in pediatrics.